Business growth challenges and opportunities facing small and medium enterprises in the Sedibeng region - Ngobena, Nadege Ngonkem (Vaal University of Technology, 2020)
The role of small and medium enterprises (SMEs) is to stimulate economic growth and competitiveness in many countries. The same applies to South Africa, where the SME sector has grown tremendously to become the engine and the lifeblood of the economy by becoming a contributor to social and economic development through employment creation and constant input to the gross domestic product. However, despite these contributions, South African SMEs face numerous challenges and opportunities which might negatively or positively impact their prospects for growth, success and sustainability. This study aimed to investigate the business growth challenges and opportunities facing SMEs in the Sedibeng Region. Through a review of literature, some challenges were identified, namely, the limited access to financial, managerial competencies, economic variable, regulations and laws, crime and corruption and lack of appropriate technology and high cost of production. Despite these challenges, SMEs are faced with some opportunities which have been created by the government to facilitate their growth, with examples including the SEDA, Ntsika Apex Fund, Khula, the National Small Business Act, Black Economic Empowerment, National Development Plan (NDP) and the Local Economic Development (LED). A four-section questionnaire was then developed using adapted measurement scales and distributed to 230 SMEs in the Sedibeng region. Respondents were selected using the non-probability convenience sampling technique. The collected data were analysed using the Statistical Packages for the Social Sciences (SPSS (Version 25.0). After testing for validity and reliability, descriptive statistics were applied in testing the perceptions of respondents towards the challenges, opportunities and business growth. Exploratory factor analysis (EFA) was applied to assess the factor structure of the collected data. Pearson correlations were used to test for the strength and direction of associations between challenges, opportunities and business growth. Regression analysis was applied in testing whether challenges, opportunities and business growth (business sustainability and external business aspects). Two SME challenges, namely, crime and technology and economic aspects, were extracted in the EFA. Additionally, two SME opportunity factors, namely ‘information technology’ and ‘environment’ were extracted in the EFA. In the same procedure, two SME growth factors, namely, external business aspects and business sustainability, were extracted. Pearson correlation analysis revealed positive and significant associations between all challenges, opportunities and business growth factors. In the regression analysis, both challenges and opportunities positively and significantly predicted SME growth. The study concludes by suggesting recommendations for limiting the impact of the identified challenges on business performance.
M. Tech (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Business; Challenges; Growth; Opportunities; Small and medium enterprices; Dissertations, Academic -- South Africa; Business enterprises -- South Africa; Organizational change; Organizational effectiveness -- South Africa; Small business -- South Africa